Protections in the recreational practice of ski and snowboard—An age and gender discussion? A case study in Spain - Mecías-Calvo, M.; Lago-Fuentes, C.; Muñoz-Pérez, I.; Picabea-Arburu, J. M.; Navarro-Patón, R. (Journal of Functional Morphology and Kinesiology, 2021)
The objective of this research was to evaluate the protections taken by ski and snowboard recreational athletes of the winter stations Sierra Nevada and Alto Campoo (Spain), regarding gender, age, and practiced sport. A total of 520 users participated, Sierra Nevada (n = 306 (58.8%)); Alto Campoo (n = 214 (42.2%)), 257 of them were men (49.4%) and 263 (50.6%) were women, from 6 to 64 years old, classified by 4 stages of development (Childhood (n = 106 (20.4%)); Teenagers (n = 110 (21.2%)); Youth (n = 101 (19.4%)); Adults (n = 203 (39.0%))). For the data collection, an Ad Hoc questionnaire was used (Socio-demographic data, use/no use of protection). The data revealed that 23.5% of the participants did not use any protection. Regarding the development stage, 1% of the children did not use any protection, neither did 3.1% of the teenagers, 6.7% of the youth, or 12.7% of the adults (p < 0.001). Regarding gender, a total of 17.1% of men did not use protection, and regarding women, 6.3% of them did not use it (p < 0.001). In relation to the practiced sport, 15.8% of the skiers did not use it against 7.7% of the snowboarders (p = 0.006). The use of protection for the practice in winter sports is not enough to reduce the injury risk in these sports and, in the worst cases, fatal accidents